Bi-allelic variants in CELSR3 are implicated in central nervous system and urinary tract anomalies - Stegmann, Jil D.; Kalanithy, Jeshurun C.; Dworschak, Gabriel C.; Ishorst, Nina; Mingardo, Enrico; Lopes, Filipa M.; Ho, Yee Mang; Grote, Phillip; Lindenberg, Tobias T.; Yilmaz, Öznur; Channab, Khadija; Seltzsam, Steve; et al. (npj Genomic Medicine, 2024)
CELSR3 codes for a planar cell polarity protein. We describe twelve affected individuals from eleven independent families with bi-allelic variants in CELSR3. Affected individuals presented with an overlapping phenotypic spectrum comprising central nervous system (CNS) anomalies (7/12), combined CNS anomalies and congenital anomalies of the kidneys and urinary tract (CAKUT) (3/12) and CAKUT only (2/12). Computational simulation of the 3D protein structure suggests the position of the identified variants to be implicated in penetrance and phenotype expression. CELSR3 immunolocalization in human embryonic urinary tract and transient suppression and rescue experiments of Celsr3 in fluorescent zebrafish reporter lines further support an embryonic role of CELSR3 in CNS and urinary tract formation.
CRIS-Team Scopus Importer:2024-03-15